Cinnamomum cassia ameliorates Ni-NPs-induced liver and kidney damage in male Sprague Dawley rats. (November 2020) - Iqbal, S; Jabeen, F; Peng, C; Ijaz, MU; Chaudhry, AS
Nickel nanoparticles (Ni-NPs) have been widely used in various industries related to electronics, ceramics, textiles, and nanomedicine. Ambient and occupational exposure to Ni-NPs may bring about potential detrimental effects on animals and humans. Thus, there is a growing effort to identify compounds that can ameliorate NPs-associated pathophysiologies. The present study examined Cinnamomum cassia ( C. cassia ) bark extracts (CMBE) for its ameliorative activity against Ni-NPs-induced pathophysiological and histopathological alterations in male Sprague Dawley rats. The biochemical analyses revealed that dosing rats with Ni-NPs at 10 mg/kg/body weight (b.w.) significantly altered the normal structural and biochemical adaptations in the liver and kidney. Conversely, supplementations with CMBE at different doses (225, 200, and 175 mg/kg/b.w. of rat) ameliorated the altered blood biochemistry and reduced the biomarkers of liver and kidney function considerably ( p < 0.05) in a dose-dependent manner. However, the best results were at 225 mg/kg/b.w. of rat. The study provided preliminary information about the protective effect of C. cassia against Ni-NPs indicated liver and kidney damages. Future investigations are needed to explore C. cassia mechanism of action and isolation of single constituents of C. cassia to assess their pharmaceutical importance accordingly.